Bilateral tuberculosis psoas abcesses - İş, Merih and Döşoğlu, Murat and Aykanat, Ömer (Cerrahpaşa Medical Journal, 2013)
The occurrence of Tuberculous psoas abscess as the presenting manifestation of tuberculosis, without evidence of active infection elsewhere is rare. We report a case of bilateral psoas abscess that was diagnosed with computed tomography in a patient who presented with low back and abdominal pain. The treatment was made with radiologically-guided percutaneous drainage followed by antituberculous drugs. As the onset of symptoms is frequently insidious and the clinical presentation is vague the diagnosis requires recognition of this disease by the physician first.